(untitled) (The Pretoria Student Law Review, 2023)
This article is inspired by a need to clarify and appraise the law relatingto the sale of goods with particular attention to the market overtprinciple in Zambia. This will be done by conducting a comparativestudy between Zambia, South Africa, and Nigeria. The articleinvestigates methods for constructing a preferable legal regime forindividuals and businesses, particularly economic transactions. Itfurther assesses the Zambian Sale of Goods Act of 1893 (56 & 57 Vict.c.71) as it relates to the market overt principle. I also highlightweaknesses in the current law requiring remedial action.